Validation of ultrasound imaging for Achilles entheseal fibrocartilage in bovines and description of changes in humans with spondyloarthritis. Issue 12 (19th August 2010) - Aydin, Sibel Zehra; Bas, Emine; Basci, Onur; Filippucci, Emilio; Wakefield, Richard J; Çelikel, Çiğdem; Karahan, Mustafa; Atagunduz, Pamir; Benjamin, Mike; Direskeneli, Haner; McGonagle, Dennis
Abstract : Background: Entheseal fibrocartilage (EF) derangement is hypothesised to be pivotal to the pathogenesis of spondyloarthritis. Ultrasound is useful for visualisation of the enthesis but its role in EF visualisation is uncertain. This work aimed to demonstrate face and content validity of ultrasound for EF visualisation both by bovine histological evaluation and EF imaging in spondyloarthritis. Methods: Achilles enthesis of 18 bovine hindfeet was visualised using a MyLab 70 ultrasound machine. The presence of tissue with EF characteristics was documented and histological confirmation was performed on five randomly selected sections using Masson trichrome staining. Ultrasound of the Achilles tendon (AT) was performed in 19 patients with spondyloarthritis and 21 healthy controls (HC). Results: The bovine EF could be visualised in all cases and seen as a thin, uncompressible, well-defined, anechoic layer between the hyperechoic bone and the hyperechoic fibrils of the enthesis both in longitudinal and transverse scans. This region corresponded to EF on histological examination. The same pattern of low signal corresponding to EF location was seen in 17/19 patients and all HC. Discontinuities of the anechoic layer around the erosions and enthesophytes were observed in the spondyloarthritis group. The thickness of the anechoic layer was not significantly different in spondyloarthritis and HC (0.5±0.1 vs 0.5±0.2 mm, p=0.9) whereas the thickness of the EF was greater in men (0.6±0.2 vs 0.5±0.1 mm; p=0.009) compared with women. Conclusion: Ultrasound can visualise EF of the AT insertion, which can be abnormal in cases of spondyloarthritis. This has implications for a better understanding of enthesopathy.